Tashmim al-Ikhtibar li Maharah al-Kalam al-‘Arabi Wafqhan li al-Ithar al-Marja’i al-Urubi al-Musytarak li al-Lughat li al-Thullab al-Jami’ah fi Indunisiya - Yasin, Agus; Tarauni, Hidia (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This study aimed to develop a speaking-skill test at the B1 of CEFR, to determine the levels of validity, reliability, and difficulty of each item, and to organize the distinguishing power of each item on the prepared test. This research was motivated by the need of Arabic Language Test as an evaluation activity that required for various purposes. Several universities in Indonesia have also intended the existence of a language test as a requirement for continuing studies to a higher degree or to a place where linguistic proficiency is required or work somewhere. Also, the most important is to upgrade students’ language skills after knowing their language abilities. This test was in the form of an aptitude test or an ability test for each skill in the Arabic language. But in the speaking skill, this test still required preparation and development of more test questions to practice. Apart from the test questions, the method of assessment and the procedures for its implementation also needed to be developed and considered. Then, the researchers took account of the need to compile and make a good test product in speaking skills by following the steps for preparing a standardized test. This was the Research and Development (R&D) with Borg and Gall’s version. The researchers used the ANATES V.0.5 2022 application for processing data and analyzing test results. Based on the results of the study, it was found that the test was feasible because it met the requirements of a good test. The trial results showed high validity and reliability values, and the level of difficulty of each item also had good distinguishing power. Out of a total of 17 questions, 13 questions were stated to be very valid, 2 questions were valid, and 2 questions were striped (-), indicating that these two questions needed to be re-analyzed on what aspects made them less valid so that the questions could be revised. These values were obtained from the results of two trials conducted in the sixth semester.